2014
DOI: 10.1007/s40264-014-0257-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a New Instrument for Detecting Preventable Adverse Drug Reactions

Abstract: The analysis of the agreements and disagreements between reviewers highlighted where improvements might be made. Given that no standard assessment tool exists in the WHO Programme, the transparency of the assessment process in this method provides a substantial basis for further development and for support in signalling possible preventability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…The case is categorized as 'not assessable' if there are no data or insufficient data for assessment (e.g. an anaphylactic reaction due to penicillin is deemed 'not assessable' if the patient's previous history of drug allergy is not documented) or if the situation is controversial [13,14].…”
Section: Study Instruments and Data Collection Approachmentioning
confidence: 99%
“…The case is categorized as 'not assessable' if there are no data or insufficient data for assessment (e.g. an anaphylactic reaction due to penicillin is deemed 'not assessable' if the patient's previous history of drug allergy is not documented) or if the situation is controversial [13,14].…”
Section: Study Instruments and Data Collection Approachmentioning
confidence: 99%
“…In our study, for all the ICSRs that reported NSAIDs as suspected, a trained multidisciplinary team of Campania Pharmacovigilance Regional Centre composed of clinical pharmacologists and pharmacists with pluriannual experience in Pharmacovigilance assessed preventability by the P-method as described elsewhere (Benkirane et al, 2015; Sessa et al, 2016a,d). The “P-method,” is an algorithm that was developed to assess the preventability of ICSRs sent through spontaneous reporting system and that was validated by several Pharmacovigilance centers in the program for International Drug Monitoring coordinated by the World Health Organization (Benkirane et al, 2015; Pal et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The “P-method,” is an algorithm that was developed to assess the preventability of ICSRs sent through spontaneous reporting system and that was validated by several Pharmacovigilance centers in the program for International Drug Monitoring coordinated by the World Health Organization (Benkirane et al, 2015; Pal et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations